1992
DOI: 10.2337/diab.41.7.872
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Glucose Tolerance in Spontaneously Hypertensive Rats: Pancreatic β-Cell Hyperfunction With Normal Insulin Sensitivity

Abstract: We used intravenous glucose tolerance tests in vivo and 3-O-methylglucose transport into skeletal muscle in vitro to assess glucose tolerance, pancreatic beta-cell function, and insulin action in 9- to 11-wk-old spontaneously hypertensive rats (SHR) and age-matched normotensive Wistar Kyoto rats (WKY). Body weight was slightly higher in the WKY (P less than 0.001), while blood pressure was elevated in the SHR (P less than 0.001). Insulin responses to intravenous glucose after 4 or 12 h of fasting in SHR were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In the present study, we confirmed the results of previous studies [14,15] In addition, a decrease in blood pressure in SHR was not always associated with a reduction in plasma insulin concentrations.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we confirmed the results of previous studies [14,15] In addition, a decrease in blood pressure in SHR was not always associated with a reduction in plasma insulin concentrations.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies showed a reduction of glucose tolerance and insulin action (18,21,29,38). On the contrary, in other studies, an increased insulin sensitivity (17,49) or no evidence of insulin resistance (7,8,17) has been observed in SHR. To clarify these contradictions, more recently, we applied the minimal model of glucose kinetics to insulinemia and glycemia data obtained from IVGTT to test whether high blood pressure causes reductions of S I and S G indexes in the SHR similar to those observed in hypertensive humans (32).…”
Section: Discussionmentioning
confidence: 83%
“…15 Although a few recent studies do not support the presence of insulin resistance in the SHR, 1617 the presence of hyperinsulinemia was confirmed even in those studies. 16 It has been suggested that nutrientstimulated hyperinsulinemia may play a role in the development of high BP in the SHR. 16 If this hypothesis were valid, then a drug intervention that decreases plasma insulin levels in the SHR should also lower BP.…”
Section: Sanjay Bhanot John H Mcneillmentioning
confidence: 99%
“…16 It has been suggested that nutrientstimulated hyperinsulinemia may play a role in the development of high BP in the SHR. 16 If this hypothesis were valid, then a drug intervention that decreases plasma insulin levels in the SHR should also lower BP. Previous studies from our laboratory have shown that vanadyl, the ( + IV) form of the trace element vanadium, exhibits effects on carbohydrate metabolism that are very similar to those of insulin.…”
Section: Sanjay Bhanot John H Mcneillmentioning
confidence: 99%